Edad del trasplante y su influencia en las características agronómicas y rendimiento en Apium graveolens L. “apio”, Zungarococha - Loreto.2019 - Cruzalegui Teco, Zoila Rosa (2022)
The research was carried out in the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3 of the road to Quistococha-LLanchama, located south of the city of Iquitos, presenting the following coordinates in UTM: 9576237 North and 682157 South and the Altitude of 126 meters above sea level. The type of research was experimental, explanatory with an independent variable (transplant age) and nine dependent variables (plant height, stem length, stem diameter, root length, plant diameter, number of petioles/plant, total plant weight, petiole/plant weight and petiole/ha weight); the objective of the research work was to determine the influence of the transplant age on the agronomic characteristics and performance of Apium graveolens L. "celery", Zungarococha-Loreto. The experimental design used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 3 rows, 8 plants/row and the sampling unit consisted of four plants/experimental unit. The transplant age in Apium graveolens L, "celery", if it significantly influences the agronomic characteristics and yield of the crop. T4 treatment (105 days) as the average transplant age exhibited the best agronomic characteristics and crop yield. The highest floor height, stem length and diameter, root length, diameter and number of petioles/plant, was the T4 Treatment (105 days). The total weight yields, petiole/plant weight and petiole/ha weight, was achieved by T4 (105 days). Treatment T4 (105 days) presented the best weight performance of petioles/ha with 5,325 t/ha, followed by T3 (75 days) with 3,636 t/ha; then the T2 (60 days) with 2.417 t/ha and finally the T1 (90 days) with 1,650 t/ha.